Database systems a practical approach to design, implementation, and management - Connolly, Thomas M.; Begg, Carolyn E. (International computer science series, 2002)
A new edition of a comprehensive guide to design, implementation and management of database systems. Features new coverage of relational algebra and relational calculus, query languages for XML, fact-finding techniques, semistructured data, and other topics.